Evaluation of the effectiveness of the training on "Home care of COVID-19 positive/suspicious patients" given to nursing students: A quasi-experimental study - Hande Sabandüzen; Öznur Kavaklı (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: This study aims to evaluate the effects of education on home care of infected or suspected COVID-19 patients on the levels of knowledge, anxiety, and awareness of nursing students in Turkey. MATERIALS AND METHODS: The study is in quasi-experimental design. A sample of 158 volunteer students studying nursing at a private university in Turkey was formed. Data were collected using, descriptive information form, "Coronavirus Anxiety Scale," "COVID-19 Awareness Scale," and the "Knowledge of COVID-19 Home Care Test." Pre-test was performed before the participants received education. Post-test was performed seven days after the intervention. SPSS version 25.0 was used for data analysis. "TREND checklist" was used for quasi-experimental/non-randomized evaluations to report the findings of the study. RESULTS: Anxiety levels decreased and the levels of awareness and knowledge on COVID-19 increased after receiving education on home care of infected or suspected COVID-19 patients (p < 0.001), indicating the effectiveness of the education. Education on home care of infected or suspected COVID-19 patients was an effective method to reduce anxiety and increase knowledge and awareness in nursing students. CONCLUSIONS: To contribute to community health, home care training can be given to nursing students, other people receiving home care, or providing home care to COVID-19 patients, infected or suspected COVID-19 patients.